The Legal-Administrative Questions of Environmental Protection in the Republic of Hungary - Benkőné Lodner, Dorottya (Discussion Papers, 1995)
In the present paper, the organisational-legal aspects of environmental protection administration are emphasised. The author attempts to show the Hungarian state control of environmental protection, the different types of territorial (local) organisations dealing with environmental protection administration. She describes the system of task and competence division in the context of local governments and among deconcentrated state administration organs and in the final part, she analyses the environmental protection activity of local governments on the basis of the legal background and practice.